Bacteria-like mesoporous silica-coated gold nanorods for positron emission tomography and photoacoustic imaging-guided chemo-photothermal combined therapy. (May 2018) - Xu, Cheng; Chen, Feng; Valdovinos, Hector F.; Jiang, Dawei; Goel, Shreya; Yu, Bo; Sun, Haiyan; Barnhart, Todd E.; Moon, James J.; Cai, Weibo
Abstract: Mesoporous silica nanoshell (MSN) coating has been demonstrated as a versatile surface modification strategy for various kinds of inorganic functional nanoparticles, such as gold nanorods (GNRs), to achieve not only improved nanoparticle stability but also concomitant drug loading capability. However, limited drug loading capacity and low tumor accumulation rate in vivo are two major challenges for the biomedical applications of MSN-coated GNRs (GNR@MSN). In this study, by coating uniformly sized GNRs with MSN in an oil-water biphase reaction system, we have successfully synthesized a new bacteria-like GNR@MSN (i.e., bGNR@MSN) with a significantly enlarged pore size (4–8 nm) and surface area (470 m 2 /g). After PEGylation and highly efficient loading of doxorubicin (DOX, 40.9%, w/w), bGNR@MSN were used for positron emission tomography (PET, via facile and chelator-free 89 Zr-labeling) and photoacoustic imaging-guided chemo-photothermal cancer therapy in vivo . PET imaging showed that 89 Zr-labeled bGNR@MSN(DOX)-PEG can passively target to the 4T1 murine breast cancer-bearing mice with high efficiency (∼10 %ID/g), based on enhanced permeability and retention effect. Significantly enhanced chemo-photothermal combination therapy was also achieved due to excellent photothermal effect and near-infrared-light-triggered drug release by bGNR@MSN(DOX)-PEG at the tumor site. The promising results indicate great potential of bGNR@MSN-PEG nanoplatforms for future cancer diagnosis and therapy. Graphical abstract: In this work, bacterial-like mesoporous silica-coated gold nanorods (bGNR@MSN) were successfully synthesized and used for positron emission tomography and photoacoustic imaging-guided chemo-photothermal combined cancer therapy. The results showed bGNR@MSN(DOX)-PEG mediated chemo-photothermal combined treatment exhibited significantly enhanced therapeutic efficacy in 4T1 tumor-bearing mice due to their excellent photothermal effects, high-efficiency DOX loading, NIR-triggered DOX release capacity and high tumor accumulation (∼10 %ID/g).